Shaping the common law from Glanvill to Hale, 1188-1688 - Barnes, Thomas G. (Thomas Garden), 1930-2010.; Boyer, Allen D. (Stanford, Calif. : Stanford Law, 2008)
This collection discusses the contributions of great common-law jurists and singular documents - namely the Magna Carta and the Laws and Liberties of Massachusetts - that have shaped common law, from its origins in twelfth-century England to its arrival in the American colonies. Featured jurists include such widely recognized figures as Glanvill, Francis Bacon, Sir Edward Coke, and John Selden, as well as less-known but influential writers like Richard Hooker, Michael Dalton, William Hudson, and Sir Matthew Hale.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Common law -- History; Common law -- England -- History; Law; Jurisprudence & general issues